Comorbidities and correlates of conduct disorder among male juvenile detainees in South Korea - Bum-Sung Choi; Johanna Inhyang Kim; Bung-Nyun Kim; Bongseog Kim (BMC, 2017)
Abstract Background The purpose of this study was to examine the rate and distribution of comorbidities, severity of childhood maltreatment, and clinical characteristics of adolescents with conduct disorder detained in a juvenile detention center in South Korea. Methods In total, 173 juvenile detainees were recruited. We analyzed the distribution of psychiatric disorders among the sample and compared the rate of comorbidities between groups with and without conduct disorder. We compared the two groups in terms of demographic and clinical characteristics, as well as severity of childhood maltreatment and psychiatric problems, using the Young Self Report (YSR) scale. Results A total of 95 (55%) of the detainees were diagnosed with conduct disorder, and 93 (96.9%) of them had at least one comorbid axis I psychiatric disorder. Detainees with conduct disorder had a higher number of comorbid psychiatric disorders; a higher rate of violent crime perpetration; had suffered more physical, emotional, and sexual abuse; and showed higher total YSR scores and externalizing behavior, somatic complaints, rule-breaking behavior, and aggressive behavior YSR subscale scores. Conclusions Conduct disorder is a common psychiatric disorder among juvenile detainees in South Korea, who tend to commit more violent crimes and show more psychopathology than detainees who do not have conduct disorder. These findings highlight the importance of diagnosing and intervening in conduct disorder within the juvenile detention system.